2010
DOI: 10.1269/jrr.09072
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Hexamethylenetetramine as an Adjuvant to Radiation and Cisplatin in the Treatment of Solid Tumors: its Independency of p53 Status

Abstract: The usefulness of hexamethylenetetramine as an adjuvant to radiation and cisplatin in the treatment of solid tumors and its dependency on the p53 status of tumor cells were examined. Human head and neck squamous cell carcinoma cells transfected with mutant TP53 (SAS/mp53), or with neo vector as a control (SAS/neo), were inoculated subcutaneously into both the hind legs of Balb/cA nude mice. The tumor-bearing mice received 5-bromo-2'-deoxyuridine (BrdU) continuously to label all proliferating (P) cells in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In subsequent studies, Masunaga et al subcutaneously injected mutantor empty vector transfected human head and neck squamous carcinoma cells into the hind legs of nude mice. They revealed that methenamine equally sensitized mutant TP53 or wild‐type tumours to chemoradiation, indicating that this agent has a great potential for chemo‐radiosensitization, as a great percentage of human cancers possess TP53 mutations …”
Section: Methenamine Synergism With Cisplatin and Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent studies, Masunaga et al subcutaneously injected mutantor empty vector transfected human head and neck squamous carcinoma cells into the hind legs of nude mice. They revealed that methenamine equally sensitized mutant TP53 or wild‐type tumours to chemoradiation, indicating that this agent has a great potential for chemo‐radiosensitization, as a great percentage of human cancers possess TP53 mutations …”
Section: Methenamine Synergism With Cisplatin and Radiationmentioning
confidence: 99%
“…In regard to total tumour cell cytocidal effects, including elimination of quiescent cells, combining methenamine with radiotherapy or cisplatin demonstrated promising therapeutic potential, especially when methenamine was administered continuously . In subsequent studies, Masunaga et al subcutaneously injected mutantor empty vector transfected human head and neck squamous carcinoma cells into the hind legs of nude mice. They revealed that methenamine equally sensitized mutant TP53 or wild‐type tumours to chemoradiation, indicating that this agent has a great potential for chemo‐radiosensitization, as a great percentage of human cancers possess TP53 mutations …”
Section: Methenamine Synergism With Cisplatin and Radiationmentioning
confidence: 99%
“…8(a) and (b) display stained sections of both tumors, control and treated by HMTA and show undamaged periphery of tissues. Some cells died in the case of HMTA, as it released formaldehyde and ammonia, [30][31][32][33] whereas the tumor that was treated by VB showed a greater inimical effect, as it damaged more tissue, which can be observed as a dark spot inside the tissue section (Fig. 7(c)).…”
Section: Histological Studymentioning
confidence: 99%
“…Under acidic conditions, its clinical efficacy has been proven in a combinatorial therapy with radiotherapy for a synergistic response to induce death in cancer cells. [29][30][31][32][33] The impact of formaldehyde was found to be enormous when combined with HMTA. The results were veried using HeLa cells and a histological study (H&A staining) performed on tumor bearing mice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, methenamine (HMTA), methenamine anhydromethylene-citrate, methenamine hippurate, methenamine mandelate and methenamine sulfosalicylate have all been reported as synthetic antibacterials [20] and as anti-infectives [21]. HMTA has also been applied in the treatment of ear canal infections in combination with anti-inflammatory and antiseptic agents [22], and as an adjuvant to radiation and cisplatin in the treatment of solid tumors [23]. In recent years HMTA has been used as base catalyst in the synthesis of phenolic gel and most recently Garci 9 a et al published a report on the use of HMTA as a base catalyst to control the porosity and pore size of resorcinol furaldehyde cryogels synthesized in t-butanol [24].…”
Section: Introductionmentioning
confidence: 99%